2018
DOI: 10.15388/infedu.2018.09
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Computational Thinking with a Music Education Context

Abstract: Computational thinking is becoming common in K-12 curricula, and at the same time there is interest in how STEM subjects can be integrated with the Arts (referred to as STEAM). There are some obvious connections between music and computation, but the idea of engaging with genuine computational thinking while also having authentic music learning experiences for students provides new opportunities.In this paper we consider ways to explore computational thinking ideas such as decomposition, patterns, abstraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
2
30
0
5
Order By: Relevance
“…Computational thinking is not limited to mathematics learning (Lockwood, Asay, DeJarnette, & Thomas, 2016;Promraksa, Sangaroon, & Inprasitha, 2014;Puspitasari, In'am, & Syaifuddin, 2019). Computational thinking is also found in music learning (Bell & Bell, 2018) and language learning (Li & Lee, 2016). These research studies show that all teachers need to have computational skills in running their classes.…”
Section: Computational Thinkingmentioning
confidence: 99%
“…Computational thinking is not limited to mathematics learning (Lockwood, Asay, DeJarnette, & Thomas, 2016;Promraksa, Sangaroon, & Inprasitha, 2014;Puspitasari, In'am, & Syaifuddin, 2019). Computational thinking is also found in music learning (Bell & Bell, 2018) and language learning (Li & Lee, 2016). These research studies show that all teachers need to have computational skills in running their classes.…”
Section: Computational Thinkingmentioning
confidence: 99%
“…In addition, the content of STEAM-based disciplines increases students' knowledge of computational thinking skills [2]. The integration of STEAM's activities into the educational practice of different laboratories allows students who are passionate about one subject to interact with other subjects, as well as facilitates interaction between teachers, based on their different expert knowledge and passions [3]. FabLab users can utilize trainees' perceptions of different dimensions to emphasize specific aspects of the design of activities to achieve learning goals [47].…”
Section: Fablab and Physical Computing For Steam Education Integratmentioning
confidence: 99%
“…For example, the EarSketch project, which integrates music with coding, found that "results reveal that students' attitudes positively and statistically significantly increased across all constructs in our Student Engagement survey, which included constructs such as computing confidence, computing enjoyment, computing perceived usefulness, motivation to succeed in computing, identity and belonging in computing, and intention to persist" (Moore et al, 2016). Several other programs have also shown strong positive results when connecting music to computer science (Barate et al, 2017;Bell & Bell, 2018;Horn et al, 2020). The Performatics program for college students described by Ruthmann et al (2010), utilized scratch to teach music students coding concepts and computational thinking while they remixed and created musical pieces.…”
Section: Literature Reviewmentioning
confidence: 76%
“…Creating engagement by using music and coding have been explored in a variety of projects and has been shown to be a powerful way to teach and learn computer science content, as well as increase coding self-efficacy (Barate et al, 2017;Bell & Bell, 2018;Horn et al, 2020;Ruthmann et al, 2010). Combining dance and coding has been explored to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%